Mental Health Scenario of Climate Migrant Women among Slum Dwellers in Dhaka City - Amjad, Karisma (International Journal of Psychotherapy Practice and Research, 2020)
Climate change is a global challenge which is likely to affect the mankind in substantial ways. Not only climate change is expected to affect physical health, it is also likely to affect mental health. Increased frequency of disasters with climate change can lead to posttraumatic stress disorder, adjustment disorder, and depression. Changes in climate may require population to migrate, which can lead to acculturation stress. It can also lead to increased rates of physical illnesses, which secondarily would be associated with psychological distress. Using a qualitative approach, this research explores the mental health status of migrant women in two urban slum areas in Dhaka city. The purpose of this study is to perform a review of existing secondary data and present mental health scenario of climate migrant women among slum dwellers and amplified gaps in knowledge regarding psychological health care system in Bangladesh. It is found that there is a lack of mental health preparedness and response in majority parts in the country specially the city slum, where aid cannot be reached to the sufferers. The paper concludes with a discussion of what can and should be done to tackle the expected mental health issues consequent to climate change and migration.
Keywords: Climate change; migration; slum dweller women; mental health; psychological health.